Bioinspired Multi‐Activities 4D Printing Objects: A New Approach Toward Complex Tissue Engineering. Issue 12 (27th September 2018) - Devillard, Chloé D.; Mandon, Céline A.; Lambert, Simon A.; Blum, Loïc J.; Marquette, Christophe A.
Abstract : 4D printing is an innovative approach which might in a near future lead to the achievement of highly complex smart materials. The authors describe a new strategy for the achievement of 4D printed objects with multiple biological activities. These activities are generated through the entrapment, during 3D printing, of two distinct enzymes (alkaline phosphatase and thrombin). These two enzymes give then the ability to the 4D printed object to generate bioactivities useful for in vitro tissue engineering. Indeed, it is shown that the entrapped alkaline phosphatase enables the localized and pre‐programmed calcification of some 3D object parts while the diffusion of thrombin from the object permits the formation of fibrin biofilm (including living cells) directly at the surface of 3D object. Both activities and enzyme behavior within the 4D printed hydrogel are characterized through enzymatic measurements, microscopy, magnetic resonance imaging (MRI), and cell seeding. Abstract : 4D printing is an innovative approach which might in a near future lead to the achievement of highly complex smart materials. The authors design and create a bioinspired multi‐activities object leading to the controlled calcification and the fibrin deposition on distinct parts of a unique 3D object. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .